RARE-08. ROSAI-DORFMAN-DESTOMBES DISEASE OF THE NERVOUS SYSTEM; A SYSTEMATIC LITERATURE REVIEW. (11th November 2019) - Alshiekh Nasany, Ruham; Reiner, Anne; Panageas, Katherine; Diamond, Eli
Abstract: INTRODUCTION: Rosai-Dorfman-Destombes disease (RDD) is a rare non–Langerhans cell histiocytosis with neurologic involvement in fewer than 5% of cases. Data about neurologic RDD is limited. Our objective was to synthesize the clinical literature about presentation, treatments, and outcomes of neurologic RDD. METHODS: A multi-database English systematic review search using keywords related to (1) histiocytosis and (2) neurologic involvement. Candidate articles were screened for clinical content. Secondary literature and cases without treatment information were excluded. Sites of involvement, presenting symptoms, treatments, and therapeutic responses were reviewed. RESULTS: Of 4768 screened, 153 articles presenting 223 patients were included. Mean age was 37.7 years (range 2–79; IQR 23.5–52.5). 149 patients (66.8%) were male and 74 (33.2%) were female. RDD lesions were located in the dura in 111 (49.8%) of cases, spine in 16.6%, brain parenchyma in 9.0%, orbit in 7.2%, calvarium in 2.7%, and in multiple sites in 13.5%. The most frequent presenting symptoms were headache in 101 (45.3%.), focal neurological deficits (32.7%), visual symptoms (31.8%), seizures (24.7%), cranial (11.7%), and cerebellar dysfunction (11.2%). Cognitive decline, masses were less common presentations. First-line treatments included resection, radiation, corticosteroids, chemotherapy, and combinations of these. First-line treatment led to complete (CR) or partial response (PR) in 153 (68.6%) of cases, stable disease in 30 (13.5%), and progressive disease in 40 (17.9%). CR or PR was observed in the calvarium in 5/6 (83.3%), dura in 82/111 (73.9%), spine in 29/37 (78.4%), orbit 8/16 (50.0%), parenchyma in 15/20 (75.0%), and multiple sites in 14/30 (46.7%). 47 (21.1%) of patients required second-line therapy. DISCUSSION: Neurologic RDD is a rare form of histiocytosis with varying sites of involvement, clinical presentations, and responses to treatment. Further investigation of effective therapies for neurologic RDD may improve outcomes for this disease.